A Revisit of the Natural Resource Curse in the Tourism Industry - Sylvain Bertelet Ngassam; Simplice Asongu; Gildas T. Ngueuleweu (African Governance and Development Institute (AGDI), 2023)
Despite a growing literature on the natural resource curse, existing studies are sparse on how real effective exchange rate, political stability and corruption shape the relationship between natural resources and tourism revenues. This study analyses both the direct and indirect effects of natural resources on tourism revenues using a panel 95 countries around the world from 1996 to 2018. First, our results indicate that natural resource dependence negatively impacts tourism revenues. Second, above certain thresholds, natural resources curse the tourism sector through the corruption of exchange rate. These results motivate recommendations aimed at maintaining political stability, reducing cumbersome regulations of tourism activities that generate corruption and the adoption of appropriate exchange rate regime is recommended but this requires further studies.
Keywords: Q34; P28; L84; 330; Corruption; Dutch diseases; natural resource; political stability; tourism revenues